Insider Trades and Demand by Institutional and Individual Investors - Sias, Richard W.; Whidbee, David A. (Review of Financial Studies, 2010)
There is a strong inverse relation between insider trading and institutional demand the same quarter and over the previous year. Our analysis suggests a combination of factors contribute to this relation. First, institutional investors are more likely to provide the liquidity necessary for insiders to trade. Second, insiders are more likely to buy low valuation and low lag return stocks while institutions are attracted to the opposite security characteristics. Last, the results are consistent with the hypothesis that insiders are more likely to view their securities as overvalued (undervalued) following a period when institutions were net buyers (sellers).